2005
DOI: 10.2298/abs0503247v
|View full text |Cite
|
Sign up to set email alerts
|

Does the coefficient of variation reflect developmental instability in plants?

Abstract: Developmental stability or homeostasis refers to the ability of an individual to produce a consistent phenotype in a given environment (Graham et al. 1993). Reduced developmental stability can result from a wide variety of environmentally (or genetically) induced perturbations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…A large number of authors have used the degree of morphological variation as an index of developmental homeostasis (Rasmuson 1960; Mitton 1978; Yezerinac et al . 1992; Sherry & Lord 1996; Veličković 2005). Moreover, several reports on plants have shown that these organisms are ideal for studying genotypic and environmental influences on developmental stability (Cowart & Graham 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of authors have used the degree of morphological variation as an index of developmental homeostasis (Rasmuson 1960; Mitton 1978; Yezerinac et al . 1992; Sherry & Lord 1996; Veličković 2005). Moreover, several reports on plants have shown that these organisms are ideal for studying genotypic and environmental influences on developmental stability (Cowart & Graham 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Selection on whole‐plant traits, such as growth, could indirectly alter the range of traits achieved across tissue ontogeny (Fiorani et al, 2000) or increase developmental instability and trait “noise” as leaves mature (Arendt, 1997). Such developmental instability, and subsequent effects on levels of trait variation among plant tissues, could also increase with hybridization (Albarrán‐Lara et al, 2010; Møller & Shykoff, 1999; Veličković & Stanković, 2005)—a common part of the domestication and improvement process (but see Gardner, 1995; Waldmann, 1999). In contrast, genome duplication, another common feature of domesticated plants (Ramanna & Jacobsen, 2003; Salman‐Minkov et al, 2016), has been found to buffer and minimize stochastic gene expression (Cook et al, 1998; Klingenberg, 2003; Soltani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Selection on whole-plant traits, such as growth, could indirectly alter the range of traits achieved across tissue ontogeny (Fiorani et al, 2000) or increase developmental instability and trait 'noise' as leaves mature (Arendt, 1997). Such developmental instability, and subsequent effects on levels of trait variation among plant tissues, could also increase with hybridization (Møller & Shykoff, 1999;Veličković & Stanković, 2005;Albarrán-Lara et al, 2010) -a common part of the domestication and improvement process (but see Gardner, 1995;Waldmann, 1999). In contrast, genome duplication, another common feature of domesticated plants (Ramanna & Jacobsen, 2003;Salman-Minkov et al, 2016), has been found to buffer and minimize stochastic gene expression (Cook et al, 1998;Klingenberg, 2003;Soltani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%